THE IMPACT OF TAZKIYATUN AN-NAFS COUNSELING IN REDUCING THE TRAUMA OF VIOLENCE EXPERIENCED BY A WIFE - Hengki Yandri; Sufyarma Marsidin; Yeni Karneli (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2022)
Background, domestic violence is a serious thing that is being experienced by many women, especially wives, which has an impact on misery and suffering physically, psychically, sexually, and neglect by a husband. So treatment is needed to reduce the trauma of violence experienced by a wife in the household by using tazkiyatun an-nafs counseling. Case Reports, a 30-year-old woman with one child received violent treatment from her husband, both physically and psychologically, and was neglected. The results from the counseling showed that the client experienced violent acts from her husband in the form of physical harm, such as being slapped and beaten, then psychically in the form of getting harsh words and leaving inner wounds and neglect because their husbands did not support them. In conclusion, counseling with a tazkiyatun an-nafs approach impacts the client in reducing the trauma of violence experienced by the client in the household. From the results of counseling, the client suggests using a spiritual approach in handling one's problems because it has proven to be effective